2011
DOI: 10.1111/j.1365-2621.2011.02572.x
|View full text |Cite
|
Sign up to set email alerts
|

Suitability for minimal processing of non‐melting clingstone peaches

Abstract: Clingstone non-melting peach cultivars (Prunus persica L. Batsch) are used primarily for canning, but their processing as fresh-cut products is also of interest. Four clingstone peach cultivars ('Andross', 'Babygold 8¢, 'Calante' and 'Romea') were evaluated for their suitability for minimal processing (washing, peeling and slicing) followed by storage for 9 days at 4°C in a modified atmosphere using microperforated films. Romea cultivar, which has low polyphenol oxidase (PPO) enzymatic activity, proved to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
6
17
0
Order By: Relevance
“…Other authors associate changes in a* as a good indicator of the surface browning because its increase is associated with an increase of surface browning in fruits such as apple or pear (Arias et al 2008;González-Buesa et al 2011); in our work, only cvs Ryan Sun and O'Henry showed an increase (Figure 1). Therefore, some surface browning was found for these TSS -total soluble solids; TA -titratable acidity; TSS/TA -acceptability index; values for the same cultivar and the same parameter followed by different letters indicate significant differences by Tukey's test (P < 0.05); *mean ± standard deviation (n = 4); **firmness values obtained from the whole fruit at the beginning of the trial (n = 10) cultivars.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Other authors associate changes in a* as a good indicator of the surface browning because its increase is associated with an increase of surface browning in fruits such as apple or pear (Arias et al 2008;González-Buesa et al 2011); in our work, only cvs Ryan Sun and O'Henry showed an increase (Figure 1). Therefore, some surface browning was found for these TSS -total soluble solids; TA -titratable acidity; TSS/TA -acceptability index; values for the same cultivar and the same parameter followed by different letters indicate significant differences by Tukey's test (P < 0.05); *mean ± standard deviation (n = 4); **firmness values obtained from the whole fruit at the beginning of the trial (n = 10) cultivars.…”
Section: Resultssupporting
confidence: 51%
“…Some authors evaluate browning using (L*) and (h°) as good indicators of the surface browning because their decrease is associated with an increase in the intensity of browning of minimally processed fruits such as apple, pear and peach (González-Buesa et al 2011). However, L* and h° values presented an increase for most of the cultivars, this could be related to the development of whitish colour of the sliced surface.…”
Section: Resultsmentioning
confidence: 99%
“…However, this decrease was more intensive for the latter. This fact could be explained by the fastened respiratory activity in wounded tissues, as it happened in minimally processed clingstone peach (González-Buesa et al 2011). Consequently, there was an increase in AI for all samples.…”
Section: Resultsmentioning
confidence: 99%
“…For nectarine (Fig. 4a), there was a considerable decrease from d 0 to 3, probably due to PPO activity which could speed up phenolic degradation in the presence of oxygen due to the mild MAP obtained (González-Buesa et al 2011). Early and medium cultivars offered similar TPC, whereas 'Late Fire', that is, the late cultivar, had higher TPC when compared with the remainder at the same day of storage.…”
Section: Browning Potentialmentioning
confidence: 99%
See 1 more Smart Citation